Students’ Perception towards Problem-Based Learning Applied in an Essay Writing Class: Challenges and Benefits - Yulitriana, NFN; Emeral, NFN (SUAR BETANG, 2024)
This study aimed to investigate how students perceived Problem-Based Learning (PBL) when applied in an essay writing class of an EFL classroom. The study focused on understanding the challenges and benefits that students observed during the PBL process. The study used survey research with a one-shot design. The procedures followed included planning, defining the population, sampling, constructing the instrument, conducting the survey, and processing the data. The study was conducted in an English Language Education Study Program of a public university in Central Kalimantan Province (Indonesia). A total of 37 students from an Intermediate English Writing class participated in the study. A questionnaire with closed- and open-ended questions was distributed to collect the data. The results showed that despite facing challenges, the majority of the students viewed PBL positively. The challenges that students experienced during the learning process included limited knowledge and experience in the conceptual mastery, problems and solutions, lack of critical thinking and creativity, and being unfamiliar with PBL. However, students also agreed that PBL was important to be implemented, as it contributes to the quality of life and helps develop soft skills essential for now and the future. Additionally, students found PBL helpful in completing the essay assigned for the subject.AbstrakPenelitian ini bertujuan menginvestigasi bagaimana mahasiswa memahami Pembelajaran Berbasis Masalah ketika diaplikasikan di kelas menulis esai di ruang kelas pembelajaran Bahasa Inggris sebagai bahasa asing. Fokus penelitian ini ialah memahami tantangan dan manfaat yang mahasiswa amati selama proses pelaksanaan PBL. Penelitian ini menggunakan penelitian survei dengan desain one-shot. Prosedurnya meliputi merencanakan, mendefinisikan populasi, menentukan sampel, menyusun instrumen, melaksanakan survei, dan mengolah data. Penelitian ini dilaksanakan di Program Studi Pendidikan Bahasa Inggris dari salah satu universitas negeri di Provinsi Kalimantan Tengah (Indonesia). Sebanyak 37 mahasiswa dari kelas Menulis Bahasa Inggris Terampil berpartisipasi dalam penelitian ini. Kuesioner yang berbentuk pertanyaan tertutup dan terbuka disebarkan untuk mengumpulkan data. Hasil penelitian menunjukkan bahwa walaupun menghadapi tantangan pada saat pelaksanaan pembelajaran, mayoritas mahasiswa memiliki pandangan positif terhadap PBL. Tantangan yang dihadapi mahasiswa selama pembelajaran meliputi pengetahuan dan pengalaman yang terbatas pada penguasaan konseptual, masalah dan solusinya, kurangnya berpikir kritis dan kreatif, dan tidak terbiasa dengan PBL. Namun, mereka juga setuju bahwa PBL penting untuk diimplementasikan karena berkontribusi pada kualitas hidup dan membantu mengembangkan keterampilan lunak yang berguna untuk kehidupan. Sebagai tambahannya, mahasiswa menganggap PBL dapat membantu mereka juga mendapatkan bantuan untuk merampungkan esai pada mata kuliah tersebut.